The MNB's house price index methodology - Ádám Banai; Nikolett Vágó; Sándor Winkler (Magyar Nemzeti Bank, 2017)
This study presents the detailed method of the MNB's house price index and the results of the new price indices. The index family is considered to be a novelty among Hungarian housing market statistics in several regards. Firstly, the national index was derived from a database starting in 1990, and thus the national index is regarded as the longest in comparison to the house price indices available so far. The long time series allows us to observe and compare the real levels of house prices across several cycles. Another important innovation of this index family is its ability to capture house price developments by region and settlement type, which sheds light on the strong regional heterogeneity underlying Hungarian housing market developments.
Keywords: C43; R21; R31; 330; housing market; house price index; hedonic regression